Development of Augmented Reality Learning Media Based on the Subak System to Improve Elementary Science Learning - I Putu Eka Indrawan; Ni Nyoman Parmithi; Ni Luh Putu Yesy Anggreni (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and examine the effectiveness of Subak system–integrated Augmented Reality (AR) media as a form of Balinese local wisdom in elementary science learning. The research employed a Research and Development (R&D) method using the ADDIE model and involved 44 third-grade students of SD Negeri 18 Denpasar as trial participants. The AR media was designed to visualize the water cycle through three-dimensional representations linked to Subak elements, including dams, irrigation channels, and rice fields. The effectiveness of the developed AR media was evaluated using a one-group pretest–posttest design. Students completed a cognitive achievement test on water cycle concepts before and after the implementation of the AR media. Learning improvement was analyzed using normalized gain (N-gain) scores and a paired-sample t-test to determine the statistical significance of the observed gains. The results indicate that the developed AR media demonstrates a very high level of validity and is effective in improving students’ science learning outcomes. Beyond cognitive gains, the media enhances contextual learning, fosters environmental awareness, and strengthens students’ appreciation of local wisdom. These findings confirm that integrating AR technology with the Subak system provides a meaningful and innovative approach to elementary science learning, aligning with the demands of digital-era education.